EMIL STAN, CLASS MANAGEMENT AND DIGITAL NATIVES. FUNDAMENTALS FROM THE PERSPECTIVE OF NEUROSCIENCES. Iaşi, Institutul European Publishing House, 2021, 201 pages, ISBN 978-606-24-0320-1 - Gina-Florentina TUDORACHE; Mihaela-Gabriela BADEA (National Centre for Policy and Evaluation in Education, 2022)
Book review